Representations of Banjar ethnicity and religious identity in Anang Ardiansyah's song lyrics: A Paul Ricoeur hermeneutic approach - Subroto, Wisnu; Nurdin, Encep Syarief; Subiyakto, Bambang; Milyartini, Rita (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
Regional songs serve as repositories of cultural values and identity markers, yet limited scholarly attention has examined their role in transmitting religious and social values within specific ethnic communities. This study applies Paul Ricoeur's three-stage hermeneutic framework—explanation, understanding, and appropriation—to analyze four purposively selected songs by Anang Ardiansyah: Batasmiyah, Bismillah Kata Bamula, Puhun Rambai, and Paris Barantai. Selection criteria included: (1) representation of different thematic elements (religious practice, cultural identity, social solidarity, environmental connection), (2) widespread recognition within Banjar communities, and (3) availability of complete lyrical texts. The explanation stage involved literal textual analysis, understanding examined cultural-contextual meanings within Banjar Islamic traditions, and appropriation explored contemporary relevance for cultural preservation. Analysis reveals three primary symbolic domains: (1) religious integration through ritual terminology ("Bismillah kata bamula", "batapung tawar") demonstrating Islamic-Banjar cultural synthesis, (2) social solidarity mechanisms embedded in zakat and gotong royong references that prescribe communal responsibility, and (3) place-based identity construction through geographical markers ("Kotabaru gunungnya bamega") and natural symbols (rambai tree) that anchor cultural belonging. The study's theoretical contribution lies in demonstrating how Ricoeur's hermeneutic appropriation stage can illuminate the contemporary transmission of traditional values through musical narratives. These findings provide empirical evidence for integrating Anang Ardiansyah's compositions into formal Islamic education curricula as supplementary materials for akhlaq (character) instruction, and suggest developing community-based cultural workshops using these songs as discussion frameworks for intergenerational value transmission among Banjar diaspora communities.